Subjective Health Cognition, Well-being, and Smoking and Drinking Behaviors among adolescents - Park, Min-Hee (Advances in Social Sciences Research Journal, 2022)
This study aimed to examine the relationship between subjective health cognition, well-being, and smoking and drinking behaviors among adolescents in one region of South Korea. The data used in this study were collected from adolescents in one region and analyzed using secondary analysis. The present study found that smokers had lower subjective health cognition scores than nonsmokers (t=10.200, p<0.001) and that drinkers had lower subjective health cognition scores than nonsmokers (t=5.422, p=0.001). In terms of subjective well-being, smokers scored lower than nonsmokers (t=12.234, p<0.001), and drinkers had lower subjective well-being scores than nonsmokers (t=10.582, p<0.001). Therefore, it is necessary to promote the health status and well-being of adolescents through smoking and drinking prevention education.